Implementation of simulation-based laboratory experiment using MATLAB Simulink Tool for Pulse Code Modulation (PCM) in digital communication course / Rina Abdullah ... [et al.] - Abdullah, Rina; Ja’afar, H.; Md Enzai, Nur Idawati; Ismail, Nuraiza (2017)
Most engineering students have been having difficulties in understanding the fundamentals of engineering courses in classroom. To tackle this problem, the use of simulation-based lab was introduced in teaching and learning process. This paper discusses the implementation of simulationbased laboratory experiment using Matlab Simulink Tool for Pulse Code Modulation (PCM) in Digital Communication course, in order to give them clearer understanding of the theoretical concept that they have learned in class for practical application. Matlab Simulink is used to help the engineering students in having good understanding of basic PCM. To demonstrate the capability of the tool, the block diagram of PCM is constructed and simulated by using Matlab Simulink. The process involved to design PCM via MATLAB Simulink is composed of Simulink simulator block set. Simulink simulator block set includes input sources, scope, sample and hold circuit, quantizer and multiplexing. There are three important steps of PCM processes including sampling, quantizing and encoding. Each characteristic of PCM process in Matlab Simulink is analyzed and then compared with the theory. It is shown that these theoretical results coincide with the simulation results and it achieved 100% accuracy.